Major components of the KARRIKIN INSENSITIVE2-dependent signaling pathway are conserved in the liverwort Marchantia polymorpha. Issue 7 (11th April 2021) - Mizuno, Yohei; Komatsu, Aino; Shimazaki, Shota; Naramoto, Satoshi; Inoue, Keisuke; Xie, Xiaonan; Ishizaki, Kimitsune; Kohchi, Takayuki; Kyozuka, Junko
Abstract: KARRIKIN INSENSITIVE2 (KAI2) was first identified as a receptor of karrikins, smoke-derived germination stimulants. KAI2 is also considered a receptor of an unidentified endogenous molecule called the KAI2 ligand. Upon KAI2 activation, signals are transmitted through the degradation of D53/SMXL proteins via MAX2-dependent ubiquitination. Although components in the KAI2-dependent signaling pathway, namely Mp KAI2A and Mp KAI2B, Mp MAX2, and Mp SMXL, exist in the genome of the liverwort Marchantia polymorpha, their functions remain unknown. Here, we show that early thallus growth is retarded and gemma dormancy in the dark is suppressed in Mp kai2a and Mp max2 loss-of-function mutants. These defects are counteracted in Mp kai2a Mp smxl and Mp max2 Mp smxl double mutants indicating that Mp KAI2A, Mp MAX2, and Mp SMXL act in the same genetic pathway. Introduction of Mp SMXL d53, in which a domain required for degradation is mutated, into wild-type plants mimicks Mp kai2a and Mp max2 plants. In addition, the detection of citrine fluorescence in Nicotiana benthamiana cells transiently expressing a SMXL-Citrine fusion protein requires treatment with MG132, a proteasome inhibitor. These findings imply that MpSMXL is subjected to degradation, and that the degradation of MpSMXL is crucial for MpKAI2A-dependent signaling in M. polymorpha . Therefore, we claim that the basic mechanisms in the KAI2-dependent signaling pathway are conserved in M. polymorpha . Abstract : Functions of genes in the KARRIKIN INSENSITIVE2-dependent signaling pathway are conserved in the liverwort Marchantia polymorpha and control early development of the thallus.